In situ experiments and seismic analysis of existing buildings. Part II Seismic integrity threshold. - Boutin, C.
The interest of in situ measurements (presented in Part I paper) for a seismic assessment of existing buildings is analysed in this paper. It is shown that the experimental modal characteristics obtained on regular concrete structures are described successfully by suited Timoshenko beam modelling. For a given structure, taking into account the experimental data, the corresponding beam model and choosing the maximum tensile strain of concrete as damage criterion for key structural elements, a maximum level of the ground acceleration can be determined. This so-called seismic integrity threshold is directly related to the onset of structural damages. This new approach is illustrated on one of the studied buildings. The advantages of using ambient vibration survey for the vulnerability assessment of existing buildings are discussed.
Keywords: In situ test monitoring; Existing buildings; Ambient variations; Timoshenko beam; Seismic integrity threshold